Filter paper solid-phase radioimmunoassay for human rotavirus surface immunoglobulins. - Watanabe, H (1977)
A filter paper solid-phase radioimmunoassay has been developed. Filter paper disks adsorbed a large amount of rotavirus and serum globulin and gave small mean variation of coating and low background binding. The rotavirus isolated from stools from infants with acute enteritis 1, 3, and 4 days after onset of symptoms was shown to be already covered with immunoglobulin G (IgG), IgA, and IgM antibodies by this radioimmunoassay, by immunoelectrophoresis, and by immune electron microscopy. The immunoglobulins covering the virus particle were partially separated during 125I labeling and eluted at the position expected for IgG during Sephadex G-200 gel filtration. Rabbit antiserum prepared against purified fecal rotavirus contained not only rotavirus antibodies but also a fairly large amount of immunoglobulin antibody, reflecting the antibodies on the rotavirus particle surface.